Improving Pancasila Education Learning Outcomes through the Example Non-Example Model in Grade III SDN 40 Sei Lareh Padang - Aisha Dewi Andjarmi.A Aisha Dewi; Etri Wahyuni; Reinita; Desyandri (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to improve students’ learning outcomes in Pancasila Education through the implementation of the Example Non Example learning model. The background of this study was the low learning outcomes, activeness, and participation of Grade III students in the learning process at SDN 40 Sei Lareh, Padang City. This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the teacher and 26 Grade III students of SDN 40 Sei Lareh, consisting of 13 male students and 13 female students, during the second semester of the 2025/2026 academic year. Data were collected through observation, documentation, interviews, and learning outcome evaluations. The results showed that students’ average learning outcomes improved from 64.1 in the pre-action stage to 75 in Cycle I and increased further to 88.24 in Cycle II. In addition, teacher and student activities also improved significantly and reached a very good category. Therefore, it can be concluded that the Example Non Example learning model effectively improved students’ activeness and learning outcomes in Pancasila Education.